ONE Health Approach to Address Zoonotic Brucellosis: A Spatiotemporal Associations Study Between Animals and Humans - Zhou, Kun; Wu, Beibei; Pan, Hang; Paudyal, Narayan; Jiang, Jize; Zhang, Le; Li, Yan; Yue, Min (Frontiers in Veterinary Science, 2020)
Background Brucellosis is one of the most significant zoonosis over the world, threatening both veterinary and human public health. However, few studies were focused on nationwide animal brucellosis and made association with human brucellosis. Methodology and principal findings We conducted a bilingual literature search on Brucella or brucellosis in China on the two largest databases (China National Knowledge Infrastructure and PubMed) and conducted a systematic review. A total of 1,383 Chinese and 81 English publications, published between 1958 and 2018 were identified. From them, 357 publications presenting 692 datasets were subjected to the meta-analysis. The overall prevalence rate is 1.70% (95% CI: 1.66-1.74), with a declining (until the late 1990s) and rising trend (starting the early 2000s). Interestingly, the highest prevalence animal is canine (8.35%, 95% CI: 7.21-9.50), and lowest is cattle (1.22%, 95% CI: 1.17-1.28). The prevalence of Brucella in animals was unequally distributed among the 24 examined regions in China. Conclusions Brucellosis is a reemerging disease for both humans and animals in China. The observed data suggests that dogs and yaks are the leading reservoirs for Brucella. And five provinces with highest prevalence rates in animals are Hubei, Sichuan, Inner Mongolia, Fujian and Guizhou. Accordingly targeted intervention policy should be implemented to break the Brucella transmission chain between animals and humans in China.